Plasma Coagulation by Organisms Other Than Staphylococcus aureus - Bayliss, Berenice G. (1965)
Bayliss, Berenice G. (Washington State University, Pullman), and Elizabeth R. Hall. Plasma coagulation by organisms other than Staphylococcus aureus. J. Bacteriol. 89:101–105. 1965.—Approximately 200 organisms were investigated for their ability to clot human and rabbit plasma. Various anticoagulants were used in preparing the plasma: acid-citrate-dextrose, ethylenediaminetetraacetate, balanced oxalate, potassium and sodium oxalates, and heparin. Twelve organisms were found which coagulated citrated plasma in less than 8 hr: four strains of Streptococcus faecalis; two strains of S. faecalis var. zymogenes; three strains of S. faecalis var. liquefaciens; and one strain each of S. pyogenes, Escherichia coli, and Serratia marcescens. Six strains of coagulase-positive Staphylococcus were selected for use as controls. Experiments were performed to determine the mechanism by which these microorganisms coagulated citrated plasma. As this was the only plasma clotted, it was presumed that the citrate was utilized by the microorganisms, thereby releasing the calcium which was then made available so that normal physiological clotting could occur. To test this hypothesis, a chromatographic method was employed to determine the presence or absence of citrate. Coagulation tests, by use of increasing amounts of citrate, showed a linear relationship between the amount of citrate in the plasma and the coagulation time. It was demonstrated that the organisms must be actively metabolizing to clot citrated plasma. Proof for this was obtained by using a cell-free filtrate, to which thimerosal had been added to inhibit growth, instead of whole cultures for the coagulation test. Only the coagulase-positive staphylococci coagulated the citrated plasma under these conditions. From the results obtained, it was concluded that plasma coagulation by these organisms was by citrate utilization.